2013
DOI: 10.1038/cddis.2013.217
|View full text |Cite
|
Sign up to set email alerts
|

Saikosaponin-d, a novel SERCA inhibitor, induces autophagic cell death in apoptosis-defective cells

Abstract: Autophagy is an important cellular process that controls cells in a normal homeostatic state by recycling nutrients to maintain cellular energy levels for cell survival via the turnover of proteins and damaged organelles. However, persistent activation of autophagy can lead to excessive depletion of cellular organelles and essential proteins, leading to caspase-independent autophagic cell death. As such, inducing cell death through this autophagic mechanism could be an alternative approach to the treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
155
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(160 citation statements)
references
References 62 publications
5
155
0
Order By: Relevance
“…Studies have reported that cytotoxic drugs can induce autophagic cell death when the apoptotic pathway is non-functional (32,37). In this study, Dp44mT was found to induce classical markers of both autophagy (Fig.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Studies have reported that cytotoxic drugs can induce autophagic cell death when the apoptotic pathway is non-functional (32,37). In this study, Dp44mT was found to induce classical markers of both autophagy (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…In contrast, previous studies have also reported a prodeath function of persistent autophagy where blocking the autophagic response using the inhibitor 3-methyladenine or the silencing of autophagy genes ATG5, ATG7, and BECN1 inhibited cell death (35,36). Furthermore, in response to various agents, apoptosis-resistant fibroblasts undergo cell death associated with autophagosome/autolysosome accumulation (37,38). These findings indicate the role of autophagic cell death as an alternative death mechanism to apoptosis (37,38).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…76,77 Chemotherapy-induced inhibitory effects on cell viability and cell proliferation usually leads to the demise of cancer cells, which can be mediated by either apoptotic or autophagic pathways. Previous studies have indicated that autophagy can act as both an inhibitor and enabler of programmed cell death.…”
Section: Cis and Rgo-agnps Synergistically Induce Autophagymentioning
confidence: 99%
“…It has been reported that the overexpression of genes encoding core components of autophagic pathways, such as Beclin 1, can inhibit various cancer types (9), and the induction of autophagy with the use of chemotherapy and radiotherapy helps to remove damaged and mutated cells, thereby reducing tumor size (10). In addition, autophagy is suggested to be an effective approach to alleviate treatment resistance in apoptosis-defective tumor cells (11). Although the definite mechanism underlying autophagic cell death still remains to be elucidated, autophagy can function as a suppressor of cancer, which makes it a promising therapeutic target.…”
Section: Introductionmentioning
confidence: 99%